TRANSFORMING PESANTREN ADOLESCENTS INTO ANTI-BULLYING AGENTS THROUGH THE BULLY BLOCKING PROGRAM: TRANSFORMASI REMAJA PESANTREN SEBAGAI AGEN ANTI-BULLYING DENGAN PROGRAM BULLY BLOCKING - Yuhbaba, Zidni Nuris; Suswati, Wahyi Sholehah Erdah (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Bullying is a significant issue affecting adolescents in both schools and islamic boarding schools (pesantren). It has detrimental effects on academic performance, social skills, and mental health for both bullies and victims. The "bully blocking" program takes a culturally relevant approach to equip adolescents with the necessary skills to prevent bullying. Objective: Our goal is to cultivate a group of adolescents to serve as active anti-bullying agents, enabling them to understand and combat bullying within their pesantren community. Method: The program consists of education, skill building training, and evaluations conducted through knowledge questionnaires and observational assessments before and after the program. Results: Participants demonstrated notable improvements in their bullying prevention skills. The percentage of those categorized as "good" increased from 22.2% to 44.4%, while those categorized as "very good" rose from 4.4% to 15.5%. Conclusion: The program achieved a significant enhancement in knowledge and skills for bullying prevention. It is crucial for the pesantren to continue supporting these initiatives through ongoing monitoring and evaluation, thereby fostering a safer environment for all students.